1995
DOI: 10.1152/jappl.1995.79.4.1181
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic respiratory responses attenuated by ablation of the cerebellum or fastigial nuclei

Abstract: The general contribution of the cerebellum to hypoxic respiratory responses and the special role of the fastigial nucleus (FN) in the hypoxic respiratory reflex mediated via peripheral chemoreceptors were investigated in anesthetized and spontaneously breathing cats. Seven cats were exposed to isocapnic progressive hypoxia before and after cerebellectomy by decreasing the fractional concentration of end-tidal O2 (FETO2) from 15 +/- 0.3% to 7% while maintaining the pressure of end-tidal CO2 at a constant level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 0 publications
6
28
0
Order By: Relevance
“…Therefore, DVH could be the results of diminishing the carotid chemoreceptor-mediated excitatory response and/or strengthening hypoxic central depression. Intracarotid injection of cyanide or doxapram has been demonstrated to elevate ventilation mainly via activating peripheral chemoreceptors (25,36,43). Our data that the ventilatory responses to these selective stimuli were inhibited by Ova exposure convincingly demonstrated that DVH was generated, at least partially, by attenuating the carotid chemoreceptor-mediated respiratory response.…”
Section: Dvh In Ova Guinea Pigs Involves At Least Partially the Supsupporting
confidence: 59%
See 1 more Smart Citation
“…Therefore, DVH could be the results of diminishing the carotid chemoreceptor-mediated excitatory response and/or strengthening hypoxic central depression. Intracarotid injection of cyanide or doxapram has been demonstrated to elevate ventilation mainly via activating peripheral chemoreceptors (25,36,43). Our data that the ventilatory responses to these selective stimuli were inhibited by Ova exposure convincingly demonstrated that DVH was generated, at least partially, by attenuating the carotid chemoreceptor-mediated respiratory response.…”
Section: Dvh In Ova Guinea Pigs Involves At Least Partially the Supsupporting
confidence: 59%
“…To test the effect of Ova exposure on the peripheral chemoreceptors-mediated ventilatory responses, both groups of animals were randomly exposed to intracarotid injection of sodium cyanide (20 g) and doxapram (2 mg) 5 min after pure N 2 exposure. These stimuli have been demonstrated to augment ventilation predominately via activating peripheral chemoreceptors (25,36,43) without systemic hypoxia. Inhalation of hypercapnic gas mixtures (7% CO 2-21% O2-balance N2) for 5 min was subsequently applied to stimulate central chemoreceptors.…”
Section: Methodsmentioning
confidence: 99%
“…Also in anesthetized mammals, electrical or chemical stimulation of the CFN increases breathing (30,218,219,352,357,358). Moreover ablation of the CFN attenuates the respiratory responses to hypercapnia and hypoxia (360,361). Finally, the CFN contains respiratorymodulated neurons responding to hypercapnia and hypoxia (145,219,359).…”
Section: Role Of the Cerebellummentioning
confidence: 99%
“…Deep cerebellar nuclei project to more rostral sites, including the midbrain and thalamus (Person et al, 1986); a major projection directly inputs to the rostral ventral respiratory cell group in rodents (Gaytan and Pasaro, 1998). The fastigial nuclei play critical roles in mediating compensatory responses to low blood pressure (Lutherer et al, 1983), and responses to hypoxia (Xu et al, 1995), and show neuronal responsivity to CO 2 (Xu and Frazier, 1997). Dysregulation of fastigial output has the potential to lead to aberrant sympathetic and parasympathetic control, resulting in such characteristics of CCHS as the absence of "dipping" of blood pressure during sleep , undampened blood pressure responses to syncope to postural changes or thoracic pressure manipulations (Weese-Mayer et al, 2001), and diminished heart rate variation to cold pressor challenges (Kim et al, 2002).…”
Section: Cerebellar Regionsmentioning
confidence: 99%